The Influence of Principal Leadership and Teacher Work Culture on the Work Loyalty of Elementary School Teachers in Cluster IV, Bukit Kapur District, Dumai City - Suarni, Suarni; Azhar, Fadly; Mahdum, Mahdum (Journal of Educational Sciences, 2022)
This study aims to determine the effect of principal's leadership on teacher work loyalty, the influence of teacher work culture on teacher work loyalty, and find out whether there is an effect of principal leadership and teacher work culture together on teacher work loyalty. The research method used is a survey using a quantitative descriptive approach. The research population of all elementary school teachers in Cluster IV, Bukit Kapur sub-district, Dumai City was 117 teachers, with a total sample of 91 teachers. The sampling technique used is Simple Random Sampling. Data collection techniques are carried out using a questionnaire. The results of the study indicate that there is a direct positive influence of principal's leadership on teacher work loyalty, there is a direct positive influence of teacher work culture on teacher work loyalty and there is an influence of principal's leadership and teacher work culture on teacher work loyalty together.